Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Implications and impacts of aligning regional agriculture with a healthy diet - Ryan T. Sharp; Angelina Sanderson Bellamy; Adrian Clear; Samantha Mitchell Finnigan; Ella Furness; Elliot Meador; Helen Metcalfe; Susanna Mills; Kevin Coleman; Andrew P. Whitmore; Alice E. Milne (Journal of Cleaner Production, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics of bacterial blight disease in resistant and susceptible rice varieties - Jennifer T. Niones; Ryan T. Sharp; Dindo King M. Donayre; Eula Gems M. Oreiro; Alice E. Milne; Ricardo Oliva (European Journal of Plant Pathology, 2022)
Bacterial blight ( X. oryzae pv. oryzae ) is a serious disease in rice across the world. To better control the disease, it is important to understand its epidemiology and how key aspects of this (e.g. infection efficiency, and spatial spread) change according to environment (e.g. local site conditions and season), management, and in particular, variety resistance. To explore this, we analysed data on the disease progress on resistant and susceptible varieties of rice grown at four sites in the Philippines across five seasons using a combination of mechanistic modelling and statistical analysis. Disease incidence was generally lower in the resistant variety. However, we found no evidence that the primary infection efficiency was lower in resistant varieties, suggesting that differences were largely due to reduced secondary spread. Despite secondary spread being attributed to splash dispersal which is exacerbated by wind and rain, the wetter sites of Pila and Victoria in south Luzon tended to have lower infection rates than the drier sites in central Luzon. Likewise, we found spread in the dry season can be substantial and should therefore not be ignored. In fact, we found site to be a greater determinant of the number of infection attempts suggesting that other environmental and management factors had greater effect on the disease than climate. Primary infection was characterised by spatially-random observations of disease incidence. As the season progressed, we observed an emerging short-range (1.6 m–4 m) spatial structure suggesting secondary spread was predominantly short-range, particularly where the resistant variety was grown.

Longitudinal Variation in Rock Climbing Impacts in the Red River Gorge Area of the Daniel Boone National Forest - Dani T Dagan; Ryan L Sharp; Nicholas Walendziak (Journal of Forestry, 2019)